Konsep Desentralisasi dalam Pelayanan Publik: (Studi Kasus Inovasi Samsat Care di Kota Makassar) - Fahlevy, Muhammad Reza; Burhanudin, Burhanudin; Fahlevy, Reza; Burhanuddin (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2022)
This study aims to look at the concept of decentralization in public services which takes a case study of the innovation of Samsat Care services in Makassar City. This type of research is a qualitative descriptive research using a literature study approach. The results of this study indicate that the concept of decentralization in services, especially in the realm of innovation in Samsat Care services in the city of Makassar, has been implemented well. The collaboration between the National Police, the Provincial Revenue Service, and PT Jasa Raharja (Persero) has been going well so that one of the positive impacts is that it can increase Regional Original Income (PAD). This can be used as evidence that decentralization can have a significant impact on the economy of a region, one of which is the innovation of Samsat Care services in Makassar City.